Aniline dissociation reaction-time developed surface composites on severe plastic deformed aluminum through surface mechanical alloying - Mohamed Refaat Ebrahim; Emad Al Ashkar (Next Materials)
Time dependent dissociation-reactions were detected due to aniline dissociation though surface mechanical alloying ‘SMA’ on pre-mechanically activated aluminum. SMA time increase from 0 to 10 min SMA in steps of 2.5 min have formed Al2.85O3.45N0.55 oxynitride stable compound phase until 10 min-SMA. Unexpectedly, the organometallic tetraaluminum sesquihydrazide C12H48Al4N12 complex compound was formed with previously formed Al2.85O3.45N0.55 at room-temperature after 10 min-SMA on Al substrate with aniline. Considering the maximum 10 min-SMA time processed Al surface contains all previously formed phases, where each formed phase after 2.5, 5 and 7.5min-SMA should have participated in forming the following phases in next SMA time range. Surface dissociation-reaction time development was detected and followed using X-Ray Diffraction at a grazing incidence 'GIXRD' qualitative identification. SiO2, FeN, TiAl, Al4Cu9 and Al35.472Cu47.792 phases were identified due to impurities existence, those were changing their depth from Al substrate’s surface as SMA time increases. Concluding that Al-Aniline dissociation-reaction time dependent surface composites containing aluminum nitrides as well as organometallics can be obtained by controlling Al substrate impurities content, surface nano-crystallization through mechanical activation and ‘SMA’ processing time.